Valoración del riesgo de desarrollar diabetes mellitus tipo 2 a través del Test de Findrisk en la población de la cabecera cantonal del cantón Chaguarpamba. - Cuenca Cuenca, Eliana Marcela (2017)
Type 2 diabetes mellitus is a metabolic disorder of multiple etiologies, characterized by chronic hyperglycemia, but it is preventable. The global Diabetes figures are alarming for which numerous studies have been proposed to work on risk factors, among which is inheritance, sex, age, overweight among others, to decrease their incidence, through prevention, and nowadays there are various tools but the most practical and easily applicable is the Findrisk test. In the following quantitative, descriptive cross-sectional study, which was carried out with a sample of 334 individuals between 20 and 64 years of age living in the Canton Chaguarpamba Cantonal Head, where the Findrisk Test was applied with the objective of investigating the risk at 10 years to develop Diabetes Mellitus type 2, and the subsequent elaboration of a prevention proposal. With the application of this test, the following results were obtained: a slightly elevated risk in the population with 40.1%, where the main risk factors were high abdominal circumference 69.8% (n = 233), high body mass index 65.6% (n = 219), not frequent consumption of fruits and vegetables 58.4% (n = 195) and a sedentary lifestyle 38.9% (n = 130).As for the predominant gender is the female with greater emphasis on the age group between 45-54 years. In this study, it was concluded that the risk of developing diabetes mellitus at 10 years in the study population is slightly elevated and female predominance. Therefore, establishing preventive measures constitute major improvements to future health problems. Key words: Diabetes Mellitus, Risk Factors, Findrisk Test.